2005
DOI: 10.1007/s00216-004-3015-1
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of an integrated PDMS microchip incorporating an LED-induced fluorescence device

Abstract: A microfluidic device with an integrated fluorescence detection system has been developed in order to miniaturize the entire analytical system. A blue or green light-emitting diode (LED) and an optical fiber were mounted in a polydimethylsiloxane-based microchip. The performance of this device was evaluated by microchip electrophoresis. When a green LED was used as the light source, the calibration curve of Sulforhodamine-101 was linear over the range 1-100 microM. The detection limit was found to be 600 nM (2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
30
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 38 publications
0
30
0
Order By: Relevance
“…This result indicates that the sensitivity of the system is adequate to detect a low concentration of fluorescein-tagged analytes and it is in the linear response range. In comparison with others, although they used more bulky and expensive detectors and=or light sources, photomultiplier tubes (PMT) and lasers, Li et al (2004) andMiyaki et al (2005) achieved 17 ng=ml and 40 ng=ml limit of detection (LOD) for fluorescein solutions, respectively.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…This result indicates that the sensitivity of the system is adequate to detect a low concentration of fluorescein-tagged analytes and it is in the linear response range. In comparison with others, although they used more bulky and expensive detectors and=or light sources, photomultiplier tubes (PMT) and lasers, Li et al (2004) andMiyaki et al (2005) achieved 17 ng=ml and 40 ng=ml limit of detection (LOD) for fluorescein solutions, respectively.…”
Section: Resultsmentioning
confidence: 94%
“…Use of an optical fiber for microfluidic fluorescence-detection system has been reported (Li et al 2004;Miyaki et al 2005;Fu et al 2006). However, they used an optical fiber to transmit either the excitation light or the emission light, and the optical fiber was embedded inside a microfluidic card.…”
Section: Introductionmentioning
confidence: 99%
“…[25][26][27][28][29][30][31][32][33][34][35][36] In addition, we have developed a micro-fluidic device with an integrated fluorescence detection system to miniaturize the whole analytical system. 29,40 We have also developed the basic concept of a microchip enzyme sensor and a micro reactor based on the photochemical immobilization of protein on the inner wall of a microchannel. 37 From these studies, it was found that the effects of the size and the surface of the microchannel were extremely important in microanalysis.…”
Section: Introductionmentioning
confidence: 99%
“…Over the past few years, the development of newer miniaturization-driven platforms which aim to increase reaction surface-to-volume requirement and reaction kinetics through the use of microbeads [5,8], carbon-nano tubes [2,9], non-conventional solid-phase material such as capillary glass and other polymers [5][6][7][8][10][11][12] and increased sensitivity in detection systems [2,[13][14][15][16] have improved the handling of samples, ensured high-throughput and improved sensitivity while reducing time and cost to run the assays compared to traditional ELISAs. Nonetheless, they require complex instrumentation and micro-manufacturing methods which are expensive, require skilled operation and are unparalleled in terms of the number of samples that can be tested concurrently as the traditional ELISA [2].…”
mentioning
confidence: 99%
“…These rapid cycles of designing-prototype development-assessment and feedback are important considerations in the development of biomedical devices including those with potential of use in immunoassays. The use of wax-based polymers and other thermoplastics such as acrylonitrile-butadiene-styrene (ABS) and polycarbonate (PC) among others, which are easily fabricated, modified to become more hydrophilic enhancing surface-protein adsorption and disposable due to its low cost, are important aspects in the development of ELISA-based systems [5,11,14,[18][19][20][21][22][23][24]. The potential of such fabrication technologies in the development of diagnostics for infectious and other diseases and its potential impact in improving disease diagnosis, treatment, care and support, and prevention must not be excluded [25,26].…”
mentioning
confidence: 99%